2015
DOI: 10.1007/s10336-015-1269-3
|View full text |Cite
|
Sign up to set email alerts
|

The flight feather moult pattern of the bearded vulture (Gypaetus barbatus)

Abstract: Moult is an extremely time-consuming and energy-demanding task for large birds. In addition, there is a trade-off between the time devoted to moulting and that invested in other activities such as breeding and/or territory exploration. Moreover, it takes a long time to grow a long feather in large birds, and large birds that need to fly while moulting cannot tolerate large gaps in the wing, but only one or two simultaneously growing feathers. As a consequence, large birds take several years to complete a full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For large birds, the difference between the power required for sustained flight and the maximum power available is relatively small, making flight with proportionately similar moult gaps than smaller birds impossible (Tucker, 1991). Therefore birds of prey, that fly while moulting, cannot compensate for the relatively slow growth of their remiges by replacing more primaries and secondaries simultaneously (Rohwer et al, 2011;Zuberogoitia et al, 2013;2016a).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For large birds, the difference between the power required for sustained flight and the maximum power available is relatively small, making flight with proportionately similar moult gaps than smaller birds impossible (Tucker, 1991). Therefore birds of prey, that fly while moulting, cannot compensate for the relatively slow growth of their remiges by replacing more primaries and secondaries simultaneously (Rohwer et al, 2011;Zuberogoitia et al, 2013;2016a).…”
Section: Reviewmentioning
confidence: 99%
“…Intraspecific variation in moult sequence, duration and extent depends, among other factors, on the breeding cycle; the age and sex of the bird; territory quality; the status (dispersive, floater, sedentary or migrant) of each individual; latitude; local weather and climatic variation (Ydenberg et al, 2007;Newton & Dawson, 2011;Dietz et al, 2013;Zuberogoitia et al, 2016a). Moreover, it must be considered that, once grown, each feather will normally be retained for at least a year, during which it will deteriorate progressively, due to environmental conditions and individual behaviour (Zuberogoitia et al, 2013).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ryan , Zuberogoitia et al . ). Keijl () suggested that photography might be a promising way to study moult in pelagic seabirds that are difficult to catch.…”
mentioning
confidence: 97%
“…Newton 1966, Underhill & Zucchini 1988, Newton & Rothery 2009, Scherer et al 2013, Morrison et al 2015. However, such data may also be acquired with other methods such as photography, which has been used to study moult in marine mammals (McConkey et al 2002) and waders (Conklin & Battley 2011, 2012 Other studies used opportunistically taken photographs of birds in moult to complement information based on conventional methods (Snyder et al 1987, Ryan 2013, Zuberogoitia et al 2016. Keijl (2011) suggested that photography might be a promising way to study moult in pelagic seabirds that are difficult to catch.…”
mentioning
confidence: 99%